Coccidian parasites in the endangered Forest Musk Deer (Moschus berezovskii) in China, with the description of six new species of Eimeria (Apicomplexa: Eimeriidae) - Gao Yunyun; Duszynski Donald W.; Yuan Fulin; Hu Defu; Zhang Dong (Parasite, 2021)
We examined 674 fresh fecal samples from forest musk deer (Moschus berezovskii Flerov) in Sichuan and Shaanxi Provinces, China, for coccidian oocysts and 65% were infected with Eimeria spp. Previously, only four Eimeria species were known from Moschus spp. Here we describe six new Eimeria species. Eimeria aquae n. sp., in 38% deer, has ovoidal oocysts, 32.0 × 23.0 μm, micropyle (M) and scattered polar granules (PGs) of various sizes are present, sometimes oocyst residuum (OR) is present; ovoidal sporocysts, 14.1 × 7.5 μm, with Stieda body (SB) and sporocyst residuum (SR). Eimeria dolichocystis n. sp., in 11% deer; cylindroidal oocysts, 36.6 × 18.9, with a M, 1 PG and OR; ovoidal sporocysts, 13.9 × 7.7, with SB and SR. Eimeria fengxianensis n. sp., in 7% deer; ovoidal oocysts, 36.3 × 25.2, a M and PGs present but OR absent; ovoidal sporocysts, 13.9 × 7.3, with SB and SR. Eimeria helini n. sp. in 24% deer; subspheroidal oocysts, 27.0 × 24.1, OR and PGs often present, but M absent; ovoidal sporocysts, 13.5 × 7.7, with SB and SR. Eimeria kaii n. sp. in 26% deer; ovoidal oocysts, 33.2 × 20.7, M and PGs present, but OR absent; ovoidal sporocysts, 14.4 × 7.5, with SB and SR. Eimeria oocylindrica n. sp., in 17% deer; cylindroidal oocysts, 36.0 × 21.4, M and 1-2 PGs present but OR absent; ovoidal sporocysts, 13.8 × 7.7, with SB and SR. Eimeria dujiangyanensis n. nom. is proposed to replace E. moschus Sha, Zhang, Cai, Wang & Liu, 1994, a junior homonym of E. moschus Matschoulsky, 1947.